The Influence of Degree Motivation and Job Market Considerations on Accounting Students Intentions to Take the CA Certification Examination (E-Jurnal Akuntansi, 2026)
This research aims to determine the effect of degree motivation and job market considerations on the intention of accounting students to take the CA certification exam because, the increase in the number of accounting graduates that is currently happening is not accompanied by an increase in the number of Chartered Accountants (CA). While the work association is getting tighter. The research population was 543 with a total sample of 229, selected using the convenient sampling method. The data collection method is the survey method using questionnaires. The data analysis technique used is Multiple Linear Regression. The results show that degree motivation and job market considerations have a positive and significant influence on the intentions of accounting undergraduate students to take the CA certification exam.
Keywords: Motivation; Job Market Considerations; Intentions